m-3x=2x-p

Simple and best practice solution for m-3x=2x-p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-3x=2x-p equation:


Simplifying
m + -3x = 2x + -1p

Reorder the terms:
m + -3x = -1p + 2x

Solving
m + -3x = -1p + 2x

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '3x' to each side of the equation.
m + -3x + 3x = -1p + 2x + 3x

Combine like terms: -3x + 3x = 0
m + 0 = -1p + 2x + 3x
m = -1p + 2x + 3x

Combine like terms: 2x + 3x = 5x
m = -1p + 5x

Simplifying
m = -1p + 5x

See similar equations:

| 180-x=112 | | 1+-18=23.9 | | 2-3x=-34 | | 102v+16v= | | 8(4)=v(10) | | -2(5t-5)+7t=4t-8 | | 8-c=-13 | | p^3-2p+2p^3= | | 2x+3y=154 | | 2(1+4n)=-10+4n | | 2ln(5-x)=7 | | 180-(6x+4)=5x | | 4y-4-3= | | 14n-17+19+9n= | | (x-5)(3x+8)=(x+10)(x-4) | | 1x+4(-1x+3)=6 | | 32+2n=8(-6+n)+4n | | 180-(6x+40)=5x | | 2n-14=18 | | 8(-5m-1)+(2+6v)2= | | -32+5x=20 | | 6-6n=-7(4n-4) | | 126=x^2-2 | | 0.2(x)(x)-1.1x+0.5=0 | | 2s-4s=36 | | 3x-31=29 | | -35+8+y=-6+14 | | 5x+45(35-4x)=45(3x-26) | | x+5=-21 | | .5X+4Y=-1 | | 5x-5.36a= | | 4t-2+t= |

Equations solver categories